PENGGUNAAN MEDIA WAYANG TUMBUHAN DAN HEWAN UNTUK MENINGKATKAN HASIL BELAJAR IPS MATERI PERSEBARAN FLORA DAN FAUNA DI INDONESIA SISWA KELAS INKLUSI VII D TAHUN PEMBELAJARAN 2022/2023 DI SMP NEGERI 2 BONTANG - Ari Fajar Ani (LPPM Institut Pendidikan Nusantara Global, 2022)
The problems studied are, (1) increasing learning outcomes on the distribution of flora and fauna in Indonesia, (2) the effectiveness of using plant and plant puppet media to improve learning outcomes. This study aims to improve student learning outcomes on the distribution of flora and fauna in Indonesia. This type of research is classroom action research which consists of two cycles. The subject of this study was the VII D inclusion class of SMP Negeri 2 Bontang with a total of 36 students, consisting of 33 regular students and 3 students with special needs with slow learning disabilities. Researchers obtained data from test and non-test techniques. The test technique is in the form of a written test while the non-test technique is obtained from teacher observations on the learning process activities using plant and animal puppet media. Data analysis was performed with quantitative and qualitative analysis. The results of this study indicate that plant and animal puppet media can improve learning outcomes on the distribution of flora and fauna in Indonesia, this media can also bridge the cognitive gap between students with special needs and regular students, so that it can be used in inclusive classes. Judging from the increase in student learning outcomes in cycle I and cycle II. The results of the first cycle test at meeting 1 averaged 64.5 in class, increasing at meeting 2 to 74.3. The class average in cycle II meeting 1 was 81.8, which had reached KKM 75, but because this was an inclusion class that accommodated students with special needs, for the second meeting a program was prepared to strengthen the concept of the distribution of flora and fauna in Indonesia. The results of cycle II meeting 2 all students have scored above the KKM with an average of 89.0.